1998
DOI: 10.1016/s0896-6273(00)80474-2
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric Specialization in Human Dorsal Frontal Cortex and Medial Temporal Lobe for Verbal and Nonverbal Memory Encoding

Abstract: The involvement of dorsal frontal and medial temporal regions during the encoding of words, namable line-drawn objects, and unfamiliar faces was examined using functional magnetic resonance imaging (fMRI). Robust dorsal frontal activations were observed in each instance, but lateralization was strongly dependent on the materials being encoded. Encoding of words produced left-lateralized dorsal frontal activation, whereas encoding of unfamiliar faces produced homologous right-lateralized activation. Encoding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

77
415
7
12

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 744 publications
(511 citation statements)
references
References 36 publications
77
415
7
12
Order By: Relevance
“…The validity of the claim for regional and hemispheric specificity of functional deficits associated with brain lesions has received increasing support more recently from studies of functional deficits caused by small seizure foci or by surgically induced lesions in the mesial-temporal lobe (Jones-Gotman, 1986;Katz et al, 1989;Loring & Meador, 2001;Sass et al, 1990;Sass et al, 1991;Trenerry et al, 1993). Similar hemispheric specialization of medial-temporal lobe structures in subserving verbal and nonverbal tasks has been demonstrated in functional MRI studies (Kelley et al, 1998;Kirchhoff, Wagner, Maril, & Stern, 2000;Wagner et al, 1998) and PET studies (Haier et al, 1992), both of which showed selective activation of the right hippocampus during visuospatial tasks. Hemispheric specialization has also been suggested in magnetoencephalography studies that show activation of the left hippocampus during word recognition and activation of the right hippocampus during visual recognition tasks (Breier, Simos, Zouridakis, & Papanicolaou, 1999;Papanicolaou et al, 2002).…”
Section: Regional and Hemispheric Specializationmentioning
confidence: 84%
“…The validity of the claim for regional and hemispheric specificity of functional deficits associated with brain lesions has received increasing support more recently from studies of functional deficits caused by small seizure foci or by surgically induced lesions in the mesial-temporal lobe (Jones-Gotman, 1986;Katz et al, 1989;Loring & Meador, 2001;Sass et al, 1990;Sass et al, 1991;Trenerry et al, 1993). Similar hemispheric specialization of medial-temporal lobe structures in subserving verbal and nonverbal tasks has been demonstrated in functional MRI studies (Kelley et al, 1998;Kirchhoff, Wagner, Maril, & Stern, 2000;Wagner et al, 1998) and PET studies (Haier et al, 1992), both of which showed selective activation of the right hippocampus during visuospatial tasks. Hemispheric specialization has also been suggested in magnetoencephalography studies that show activation of the left hippocampus during word recognition and activation of the right hippocampus during visual recognition tasks (Breier, Simos, Zouridakis, & Papanicolaou, 1999;Papanicolaou et al, 2002).…”
Section: Regional and Hemispheric Specializationmentioning
confidence: 84%
“…Our results are inconsistent, however, with the findings of Casey et al (1998), who failed to observe laterality differences in task performance using the same task we did. 3 Kelley et al (1998) tested participants on word and line drawings of objects and faces. Left dorsal frontal activation was observed for the encoding of words, and fight dorsal frontal activation was observed for the encoding of faces.…”
Section: Discussionmentioning
confidence: 99%
“…The first six regions lie in the ventral visual pathway that participates in face processing. The right prefrontal region chosen was activated when non-famous faces were presented for encoding [Chee and Caplan, 2002;Kelley et al, 1998]. …”
Section: Imaging and Image Analysismentioning
confidence: 99%